Pengaruh Likuiditas, Aktivitas, Profitabilitas dan Leverage Terhadap Financial Distress (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2018) - Rahmadona Amelia Fitri; Syamwil Syamwil (Jurnal Ecogen, 2020)
The research aims to determine the effect of liquidity, activity, profitability and leverage on the financial distress of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The population is 161 companies with 805 data. The sample technique uses purposive sampling and simple random sampling to get a sample of 64 companies with 320 data, the number of samples used is 256 valid data and in accordance with the required criteria. Data analysis technique used logistic regression analysis. Based on the results of logistic regression analysis with a significance level of 5% the results of the study concluded: 1) Liquidity, activity, profitability and leverage affect the financial distress with a significance value of 0,000 < 0.05 and independent variables can hear iden the occurrence of the dependent variable of 83,8% . 2) Liquidity does not affect the financial distress with a significance value of 0.199 > 0.05. 3) Activities affect the financial distress with a significance value of 0.041 < 0.05. 4) Profitability affects the financial distress with a significance value of 0,000 < 0.05. 5) Leverage affects the financial distres with a significance value of 0,000 < 0.05.Keywords: liquidity, activity, profitability, leverage, financial distress.